2012
DOI: 10.1002/pon.3047
|View full text |Cite
|
Sign up to set email alerts
|

Predicting parenting stress in caregivers of children with brain tumours

Abstract: There was a high prevalence of parenting stress in caregivers of children with a brain tumour. An external locus of control and coping by accepting responsibility increased the likelihood of elevated levels of stress. Results emphasised the importance of ongoing support for parents of children with brain tumours. Intervention might helpfully be centred on strategies to increase parents' internal locus of control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 58 publications
3
21
0
1
Order By: Relevance
“…In our study, lower levels of perceived maternal emotional warmth and higher levels of maternal rejection were associated with increased levels of parenting stress. A study by Bennett, English, Rennoldson, and Starza-Smith (2012) found locus of control to be the strongest predictor of parenting stress in parents of children with brain tumors. Although this is a completely different sample, the mechanisms might be comparable.…”
Section: Discussionmentioning
confidence: 98%
“…In our study, lower levels of perceived maternal emotional warmth and higher levels of maternal rejection were associated with increased levels of parenting stress. A study by Bennett, English, Rennoldson, and Starza-Smith (2012) found locus of control to be the strongest predictor of parenting stress in parents of children with brain tumors. Although this is a completely different sample, the mechanisms might be comparable.…”
Section: Discussionmentioning
confidence: 98%
“…En cuanto a los sentimientos, los cuidadores familiares de niños con cáncer afrontan un gran impacto en su esfera emocional, lo que desencadena depresión, estrés (Bennett et al, 2013;Choi et al, 2016;Nam et al, 2016), mala calidad de vida, ansiedad (Nóbrega y Pereira, 2011), sobrecarga (Montero-Pardo et al, 2015) y sentimientos adversos como agitación, pérdida, temor, preocupación, incertidumbre, angustia, rabia, dolor, desesperación, miedo y desesperanza (Björk et al, 2015;Comaru y Monteiro, 2008;Fletcher, 2010;Flury et al, 2015;Gelesson et al, 2009;Gibbins et al, 2012;Granek et al, 2014;Vrijmoet-Wiersma et al, 2008;Silva et al, 2011;Taleghani et al, 2012;Wong y Chan, 2006).…”
Section: Insuficiencia Del Rol De Cuidador Del Niño Con Cáncerunclassified
“…Parents of children with CHD are at significantly higher risk than parents of healthy children of developing anxiety, depression, somatisation and feelings of hopelessness as a result of the psychosocial burden 27 28. Furthermore, there is evidence to suggest that these psychosocial morbidities persist in the long term 27.…”
Section: Global Health Problem Analysismentioning
confidence: 99%
“…Other forms of therapy that focus on restoring parents' ‘internal locus of control’ have also demonstrated efficacy in reducing stress levels in parents acting as the primary caregiver to a sick child 28. Involving parents in any way possible can help give them a sense of control and involvement in the treatment of their child during extended hospitalisations in the neonatal intensive care.…”
Section: Global Health Problem Analysismentioning
confidence: 99%